Social innovation in a developing country: invention and diffusion of the Brazilian cooperative incubator - Almeida, Mariza; Mello, Jose Manoel Carvalho De; Etzkowitz, Henry (International Journal of Technology and Globalisation, 2012)
The incubator model of a support structure to develop high-tech ﬁrms from academic research was imported from the USA to Brazil, where it serves a variety of economic and social purposes. The Brazilian cooperative incubator is a creative reinterpretation of the business incubator model to advance social innovation. It addresses issues of social exclusion, poverty and unemployment by empowering favela residents to create their own jobs. Having diffused broadly, the Brazilian cooperative incubator allows us to address the issue of growth in social enterprises. This paper employs a triple helix dynamic model, including government (local, regional and national), academic (different types of universities, industry (ﬁrms of varying scale and sector, industry associations) and NGOs (non governamental organizations) to explain the diffusion and expansion of this innovation in social entrepreneurship.
Keywords: Amérique latine; Libre accès

Social innovation in a developing country: invention and diffusion of the Brazilian cooperative incubator - Almeida, Mariza; Mello, Jose Manoel Carvalho De; Etzkowitz, Henry (International Journal of Technology and Globalisation, 2012)
The incubator model of a support structure to develop high-tech ﬁrms from academic research was imported from the USA to Brazil, where it serves a variety of economic and social purposes. The Brazilian cooperative incubator is a creative reinterpretation of the business incubator model to advance social innovation. It addresses issues of social exclusion, poverty and unemployment by empowering favela residents to create their own jobs. Having diffused broadly, the Brazilian cooperative incubator allows us to address the issue of growth in social enterprises. This paper employs a triple helix dynamic model, including government (local, regional and national), academic (different types of universities, industry (ﬁrms of varying scale and sector, industry associations) and NGOs (non governamental organizations) to explain the diffusion and expansion of this innovation in social entrepreneurship.
Keywords: Amérique latine; Version libre-accès Academia.edu

Entrepreneurial university dynamics: Structured ambivalence, relative deprivation and institution-formation in the Stanford innovation system - Etzkowitz, Henry; Germain-Alamartine, Eloïse; Keel, Jisoo; Kumar, Caleb; Smith, Kaden Nelson; Albats, Ekaterina (Technological Forecasting and Social Change, 2019)
Stanford is a quintessential entrepreneurial university, encouraging firm formation from existing knowledge that the university aggregates as well as new knowledge that it creates. Its founders implanted an academic institution, with scholarly and entrepreneurial ambitions, on a ranch where cattle still graze in the upper campus. In contrast to MIT's founding role in Boston, infusing new technology into an old industrial region's firms, Stanford assisted industrial development in an agricultural region and its industrial interlocutors raised the technical level of the university in mutually beneficial symbiosis (Lecuyer, 2007). The theory and practice of how to “make over” a university into an entrepreneurial actor has come to the forefront of academic and policy attention, internationally, with the European Union sponsoring development of the U-Multirank tool that includes the phenomenon (Van Vught and Ziegele, 2012) and a Brazilian post-graduate student project part of the ITHI Global Entrepreneurial University Metrics (GEUM) initiative that produced a dedicated entrepreneurial university metric (Nerves and Mancos, 2016). As an academic institution propelled to the forefront of global rankings (O'Malley, 2018), while helping create the world's leading high-tech region, Stanford University is in a radically different position from its late 19th century developing region origins. Should Stanford respond to dramatic shift in status and fortune by reverting to an Ivory Tower mode in response to critics who label it “Get Rich U.” (Auletta, 2012)? Or, should it double down on its entrepreneurial heritage and forge more extensive ties to Silicon Valley and other innovation hubs? In 2011, then Stanford President John Hennessy responded to former New York Mayor Bloomberg's request for proposal (RFP) for a university to establish an entrepreneurial campus. Intrigued by the prospect of engaging with the city's financial, art and media complexes, Stanford invested one million dollars in proposal development but eventually withdrew its bid in the face of faculty opposition to diversion of resources as well as Cornell University's munificent counter-offer in alliance with Israel's Technion (Hennessy, 2018). Instead, Hennessy inaugurated a program with an altruistic bent, funding international scholars who will, after pursuing advanced degrees at Stanford, “drive progress for humanity rather than for a select few.” Doubtless, these nascent social entrepreneurs will internalize Silicon Valley's optimistic ideology. Success, as well as entrepreneurial exuberance, creates blinders that suppress disconcerting events, at least temporarily. In the late 00's, generating 7–9 start-ups per annum, the highest rate of any university, Stanford ignored flaws in its technology transfer process that inhibited greater attainment. The research question generated may be stated as follows: how is a hidden innovation gap recognized and resolved? An attitude of, “if it's not broken don't fix it” had taken hold rather than the converse “If it's working well make it better.” Inventions that were too early-stage to be licensed and required translational research or a start-up, languished. The first author faced a dilemma in presenting such less than stellar results from a 2005 study of Stanford's Office of Technology Licensing (OTL) to the Dean of Research, its sponsor: how could such an analysis be taken seriously in the face of overweening achievement? The Dean's response was that, “OTL is not on our radar, they make more money each year.” Nevertheless, neophyte academic entrepreneurs had independently come to a similar conclusion as ours and were impelled to act. Their initiatives are the subject matter of this article. Skeptical of Stanford's relevance to aspiring universities, Jacob et al. (2003) hold that, “The reality of building an entrepreneurial university… is an arduous task for which there is no blueprint.” Yet, a potentially replicable organizational design may be discerned by changing the focal point from Silicon Valley's efflorescence to Stanford's entrepreneurial dynamic. The article proceeds as follows. Section 2 outlines a theoretical framework for the entrepreneurial university and reviews its literature. Section 3 presents a research design to investigate the “paradox of success,” its causes and cures. Section 4 presents a series of initiatives instituted to enhance the Stanford Innovation System. Section 5 formulates an organizational change thesis, linking design thinking to Institution Formation Sociology and social with technological innovation. Section 6 proposes policy measures to improve the Stanford Innovation System in particular and the entrepreneurial university model, in general. Finally, Section 6 sums up research insights, notes study limitations and outlines future research.
Keywords: Entrepreneurial; Réservé UdeM; Système d'innovation; Université; numérique

Entrepreneurial university dynamics: Structured ambivalence, relative deprivation and institution-formation in the Stanford innovation system - Etzkowitz, Henry; Germain-Alamartine, Eloïse; Keel, Jisoo; Kumar, Caleb; Smith, Kaden Nelson; Albats, Ekaterina (Technological Forecasting and Social Change, 2019)
Stanford is a quintessential entrepreneurial university, encouraging firm formation from existing knowledge that the university aggregates as well as new knowledge that it creates. Its founders implanted an academic institution, with scholarly and entrepreneurial ambitions, on a ranch where cattle still graze in the upper campus. In contrast to MIT's founding role in Boston, infusing new technology into an old industrial region's firms, Stanford assisted industrial development in an agricultural region and its industrial interlocutors raised the technical level of the university in mutually beneficial symbiosis (Lecuyer, 2007). The theory and practice of how to “make over” a university into an entrepreneurial actor has come to the forefront of academic and policy attention, internationally, with the European Union sponsoring development of the U-Multirank tool that includes the phenomenon (Van Vught and Ziegele, 2012) and a Brazilian post-graduate student project part of the ITHI Global Entrepreneurial University Metrics (GEUM) initiative that produced a dedicated entrepreneurial university metric (Nerves and Mancos, 2016). As an academic institution propelled to the forefront of global rankings (O'Malley, 2018), while helping create the world's leading high-tech region, Stanford University is in a radically different position from its late 19th century developing region origins. Should Stanford respond to dramatic shift in status and fortune by reverting to an Ivory Tower mode in response to critics who label it “Get Rich U.” (Auletta, 2012)? Or, should it double down on its entrepreneurial heritage and forge more extensive ties to Silicon Valley and other innovation hubs? In 2011, then Stanford President John Hennessy responded to former New York Mayor Bloomberg's request for proposal (RFP) for a university to establish an entrepreneurial campus. Intrigued by the prospect of engaging with the city's financial, art and media complexes, Stanford invested one million dollars in proposal development but eventually withdrew its bid in the face of faculty opposition to diversion of resources as well as Cornell University's munificent counter-offer in alliance with Israel's Technion (Hennessy, 2018). Instead, Hennessy inaugurated a program with an altruistic bent, funding international scholars who will, after pursuing advanced degrees at Stanford, “drive progress for humanity rather than for a select few.” Doubtless, these nascent social entrepreneurs will internalize Silicon Valley's optimistic ideology. Success, as well as entrepreneurial exuberance, creates blinders that suppress disconcerting events, at least temporarily. In the late 00's, generating 7–9 start-ups per annum, the highest rate of any university, Stanford ignored flaws in its technology transfer process that inhibited greater attainment. The research question generated may be stated as follows: how is a hidden innovation gap recognized and resolved? An attitude of, “if it's not broken don't fix it” had taken hold rather than the converse “If it's working well make it better.” Inventions that were too early-stage to be licensed and required translational research or a start-up, languished. The first author faced a dilemma in presenting such less than stellar results from a 2005 study of Stanford's Office of Technology Licensing (OTL) to the Dean of Research, its sponsor: how could such an analysis be taken seriously in the face of overweening achievement? The Dean's response was that, “OTL is not on our radar, they make more money each year.” Nevertheless, neophyte academic entrepreneurs had independently come to a similar conclusion as ours and were impelled to act. Their initiatives are the subject matter of this article. Skeptical of Stanford's relevance to aspiring universities, Jacob et al. (2003) hold that, “The reality of building an entrepreneurial university… is an arduous task for which there is no blueprint.” Yet, a potentially replicable organizational design may be discerned by changing the focal point from Silicon Valley's efflorescence to Stanford's entrepreneurial dynamic. The article proceeds as follows. Section 2 outlines a theoretical framework for the entrepreneurial university and reviews its literature. Section 3 presents a research design to investigate the “paradox of success,” its causes and cures. Section 4 presents a series of initiatives instituted to enhance the Stanford Innovation System. Section 5 formulates an organizational change thesis, linking design thinking to Institution Formation Sociology and social with technological innovation. Section 6 proposes policy measures to improve the Stanford Innovation System in particular and the entrepreneurial university model, in general. Finally, Section 6 sums up research insights, notes study limitations and outlines future research.
Keywords: Entrepreneurial; Réservé UdeM; Système d'innovation; Université; numérique